A Meta-Analysis of Interventions to Promote Self-Determination for Students With Disabilities. (June 2020) - Burke, Kathryn M.; Raley, Sheida K.; Shogren, Karrie A.; Hagiwara, Mayumi; Mumbardó-Adam, Cristina; Uyanik, Hatice; Behrens, Sarah
Promoting self-determination is critical to enabling young people to achieve education-related goals and positive postschool employment, community participation, and quality of life outcomes. By developing skills associated with self-determination such as choice-making, decision-making, problem solving, goal setting and attainment, planning, self-management, self-advocacy, self-awareness, and self-knowledge, students with disabilities are better prepared to make purposeful decisions and choices. We conducted a meta-analysis of the literature on interventions to promote self-determination and associated skills with students with disabilities in the school context. We analyzed the types of interventions, populations of students with whom they were implemented, outcomes, and rigor of research. Results demonstrated that interventions to promote self-determination can be effective for students across grade levels, disability labels, and settings. There remains a need for increased focus on promoting self-determination within inclusive, general education settings with students with and without disabilities and of diverse backgrounds. Future researchers should also focus on the rigor of methodological design and associated reporting when conducting school-based research. Additional implications for research and practice are discussed.